2022
DOI: 10.1371/journal.pone.0274833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contact with a dog on prefrontal brain activity: A controlled trial

Abstract: Background There is a broad range of known effects of animal contact on human mental and physical health. Neurological correlates of human interaction with animals have been sparsely investigated. We investigated changes in frontal brain activity in the presence of and during contact with a dog. Methods Twenty-one healthy individuals each participated in six sessions. In three sessions, participants had contact with a dog, and in three control sessions they interacted with a plush animal. Each session had fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Human-dog interaction improves the mental well-being of participants as suggested by [26]. Prefrontal brain activation in healthy subjects increased with the rise in interaction and closeness with a dog.…”
Section: Do Dogs Have a Place In Palliative Care?mentioning
confidence: 82%
“…Human-dog interaction improves the mental well-being of participants as suggested by [26]. Prefrontal brain activation in healthy subjects increased with the rise in interaction and closeness with a dog.…”
Section: Do Dogs Have a Place In Palliative Care?mentioning
confidence: 82%
“…In another study, participants showed higher frontal lobe brain activity when they interacted with a dog compared to a stuffed animal. In addition, frontal lobe brain activity increased as the intensity of contact with the animal increased [ 57 ]. Our study showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have compared live animals to stuffed animals in the context of AAI and outcomes are mixed. For example, research examining the activation brain activity suggests that both interaction with a live dog and a stuffed animal dog increased brain activity, but the live dog stimulated more activity than the stuffed dog ( 29 ). Another study suggests that interaction with a robot dog and a live dog can be similar regarding the effects on mood, but different when examined on a deeper cognitive attribution level ( 30 ).…”
Section: Discussionmentioning
confidence: 99%